Transcriptome Analysis Reveals the Molecular Response to Salinity Challenge in Larvae of the Giant Freshwater Prawn Macrobrachium rosenbergii - Wang, Yakun; Wei, Jie; Hong, Kunhao; Zhou, Nan; Liu, Xiaoli; Hong, Xiaoyou; Li, Wei; Zhao, Jian; Chen, Chen; Wu, Liang; Yu, Lingyun; Zhu, Xinping (Frontiers in Physiology, 2022)
Salinity is a crucial factor influencing the growth, development, immunity, and reproduction of aquatic organisms; however, little is known about the molecular mechanism of the response to salinity challenge in larvae of the giant freshwater prawn Macrobrachium rosenbergii. Herein, larvae cultured in three treatment groups with salinities of 10‰, 13‰, and 16‰ (S10, S13, and S16) were collected, and then transcriptome analysis was conducted by RNA-seq. A total of 6473, 3830 and 3584 differentially expressed genes (DEGs) were identified in the S10 vs. S13 comparison, S10 vs. S16 comparison and S13 vs. S16 comparison, respectively. These genes are involved in osmoregulation, energy metabolism, molting, and the immune response. qPCR analysis was used to detect the expression patterns of 16 DEGs to verify the accuracy of the transcriptome data. Protein–protein interaction (PPI) analysis for DEGs and microsatellite marker screening were also conducted to reveal the molecular mechanism of salinity regulation. Together, our results will provide insight into the molecular genetic basis of adaptation to salinity challenge for larvae of M. rosenbergii.